The blood of Olympus - Riordan, Rick. (Los Angeles : Disney/Hyperion, 2014)
The Greek and Roman demigods must simultaneously prevent the earth mother, Gaea, from waking and stop war from breaking out at Camp Half-Blood.
Horn Book, April 2015.
4.7
5-8
690L
Keywords: Mythology, Greek -- Juvenile fiction; Mythology, Roman -- Juvenile fiction; Gaia (Greek deity) -- Juvenile fiction; Mythology, Greek -- Fiction; Mythology, Roman -- Fiction; Gaia (Greek deity) -- Fiction; Greek mythology -- Fiction; Roman mythology -- Fiction; Camps -- Fiction; Fantasy; Fantasy fiction; Action and adventure fiction